2018
DOI: 10.1016/j.cell.2017.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Driven Phenotypic Convergence Supports Rational Treatment Strategies of Chronic Infections

Abstract: SummaryChronic Pseudomonas aeruginosa infections evade antibiotic therapy and are associated with mortality in cystic fibrosis (CF) patients. We find that in vitro resistance evolution of P. aeruginosa toward clinically relevant antibiotics leads to phenotypic convergence toward distinct states. These states are associated with collateral sensitivity toward several antibiotic classes and encoded by mutations in antibiotic resistance genes, including transcriptional regulator nfxB. Longitudinal analysis of isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
215
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(231 citation statements)
references
References 43 publications
12
215
3
1
Order By: Relevance
“…Intriguingly, strains within the same class were not necessarily evolved in the same stress nor stress category. Similar phenotypic convergence of drug resistant strains has recently been reported for Pseudomonas aeruginosa (Imamovic et al, 2018). To elucidate characteristic gene expressions for each class, we applied linear discriminant analysis (LDA) (see STAR Methods).…”
Section: Supervised Pca Reveals Modular Phenotypic Statesmentioning
confidence: 83%
See 1 more Smart Citation
“…Intriguingly, strains within the same class were not necessarily evolved in the same stress nor stress category. Similar phenotypic convergence of drug resistant strains has recently been reported for Pseudomonas aeruginosa (Imamovic et al, 2018). To elucidate characteristic gene expressions for each class, we applied linear discriminant analysis (LDA) (see STAR Methods).…”
Section: Supervised Pca Reveals Modular Phenotypic Statesmentioning
confidence: 83%
“…Quantitative studies of resistance evolution showed that these mechanisms for resistance are tightly interconnected, as demonstrated by the complicated networks of cross-resistance and collateral sensitivity among drugs (Barbosa et al, 2017;Chevereau et al, 2015;Girgis et al, 2009;Lázár et al, 2014;Suzuki et al, 2014), which is the phenomena where the acquisition of resistance to a certain drug is accompanied by resistance or sensitivity to another drug. Such interactions among resistance mechanisms result in constraints on accessible phenotypes in evolution, which could provide a basis to predict and control the resistance evolution (Furusawa et al, 2018;Imamovic et al, 2018;Lässig et al, 2017). For example, the cyclic or simultaneous use of two drugs with collateral sensitivity, to which pathogens did not easily acquire resistance simultaneously, were demonstrated to suppress resistance evolution (Munck et al, 2014;Yoshida et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, significant efforts have been devoted to designing evolutionarily sound strategies that balance short-term drug efficacy with the long-term potential to develop resistance. These approaches describe a number of different factors that could modulate resistance evolution, including interactions between bacterial cells (3,4,5,6,7,8), synergy with the immune system (9), spatial heterogeneity (10,11,12,13,14,15), epistasis between resistance mutations (16,17), precise temporal scheduling (18,19,20,21), and statistical correlations between resistance profiles for different drugs (22,23,24,25,26,27,28,29,30,31).…”
Section: Introductionmentioning
confidence: 99%
“…These anti-resistance approaches exploit different features of the population dynamics, including competitive suppression between sensitive and resistance cells (14,15), synergy with the immune system (16), precise timing of growth dynamics or dosing (17,18), responses to subinhibitory drug doses (19), and band-pass response to periodic dosing (10). Resistance-stalling strategies may also exploit spatial heterogeneity (20,21,22,23,24,25), epistasis between resistance mutations (26,27), hospital-level dosing protocols (28,29), and regimens of multiple drugs applied in sequence (28,30,18,31,19,32) or combination (33,34,35,36,37,38,39,40), which may allow one to leverage statistical correlations between resistance profiles for different drugs (41,42,43,44,39,37,45,46,47,48). As a whole, these studies demonstrate the important role of community-level dynamics for understanding and predicting how bacteria respond and adapt to antibiotics.…”
Section: Introductionmentioning
confidence: 99%